Simulated nuclear contamination scenario, solid cancer risk assessment, and support to decision - Lima, Sergio X.; Costa, Karolina P. S.; Lima, Zelmo R.; Rother, Fagner C.; Araujo, Olga M. O.; Vital, Helio C.; Brum, Tercio; Wilson, F. R. S. Junior; Amorim, Jose Carlos C.; Healy, Matthew J. F.; Andrade, Edson R. (De Gruyter, 2019)
The detonation of an (hypothetical) improvised nuclear device (IND) can generate atmospheric release of radioactive material in the form of particles and dust that ultimately contaminate the soil. In this study, the detonation of an IND in an urban area was simulated, and its effects on humans were determined. The risk of solid caner development due to radiation was calculated by taking into account prompt radiation and whole-body exposure of individuals near the detonation site up to 10 km. The excess relative risk (ERR) of developing solid cancer was evaluated by using the mathematical relationship from the Radiation Effects Research Foundation (RERF) studies and those from the HotSpot code. The methodology consists of using output data obtained from simulations performed with the HotSpot health physics code plugging in such numbers into a specific given equations used by RERF to evaluate the resulting impact. Such a preliminary procedure is expected to facilitate the decision-making process significantly.
Keywords: improvised nuclear device (IND); induced cancer; risk assessment; decsion